2018
DOI: 10.1080/20004508.2018.1429768
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation, privatisation and marketisation of Nordic comprehensive education: social changes reflected in schooling

Abstract: The Nordic countries are often perceived as a coherent group representing the Nordic model of welfare states, with a strong emphasis on the public provision of universal welfare and a strong concern with social equality. But today we see a change in the Nordic model as part of a global knowledge economy. The aim of this article is to examine education in the five Nordic countries utilising three dimensions of political change: deregulation, marketisation and privatisation. We also analyse the parallel changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 49 publications
2
66
0
1
Order By: Relevance
“…Notes 1. Generally, school choice can be defined as a policy whereby schools may select some or all of their students, and families may, to an extent, choose a school or an educational track for their children (Dovemark et al, 2018). 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notes 1. Generally, school choice can be defined as a policy whereby schools may select some or all of their students, and families may, to an extent, choose a school or an educational track for their children (Dovemark et al, 2018). 2.…”
Section: Discussionmentioning
confidence: 99%
“…Bernelius, 2013;Kupari et al, 2013;Lundahl, 2016). While not as pronounced as in, for example, Denmark and Sweden, the increase in the use of market mechanisms in the field of education is also very much evident in Finland (Berisha, Rinne, Järvinen, & Kinnari, 2017;Dovemark et al, 2018).…”
Section: Segregation Of Basic Education In Finlandmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of the Swedish school system have pointed in a similar direction, outlining an increasing tension between market interests and a 'free choice discourse', on the one hand, and an increasing differentiation between and within schools, on the other hand (e.g. Beach 2018;Dovemark et al 2018;Yang Hansen and Gustafsson 2016). Furthermore, studies show that Swedish pupils are easily influenced by market discourses when choosing upper secondary education (Lidström, Holm, and Lundstrom 2014;Lund 2008) but also that the understanding of 'freedom of choice' tends to differ between boys and girls (Asp-Onsjö and Holm 2014).…”
Section: Introductionmentioning
confidence: 94%
“…These trends are being researched and discussed on a worldwide level and questions have been raised regarding social justice, equality or marginalization outcomes, effects and consequences on educational, and learning participation, and life chances of underprivileged, disadvantaged or impoverished children and youth (Robertson & Dale, 2013). Some of the research points out the fact that in Nordic countries, for example, social differentiation and segregation between schools and social groups grew at the same time as privatization, marketization and deregulation (Beach, 2017;Dovemark et al, 2018;Östh et al, 2013). Similarly, in Chile where measures to privatize public schooling have a longer history, recent studies have shown there are high levels of school segregation (Rambla et al, 2011) while selection mechanisms for the recruitment of elite students by private schools remain in place (Belleï, 2009).…”
Section: The Transnationality Of Managerialism In Public Schoolsmentioning
confidence: 99%